2011
DOI: 10.1002/chem.201102695
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Evaluation, and Structure of Vitamin D Analogues with Furan Side Chains

Abstract: Based on the crystal structures of human vitamin D receptor (hVDR) bound to 1α,25-dihydroxy-vitamin D(3) (1,25 D) and superagonist ligands, we previously designed new superagonist ligands with a tetrahydrofuran ring at the side chain that optimize the aliphatic side-chain conformation through an entropy benefit. Following a similar strategy, four novel vitamin D analogues with aromatic furan side chains (3a, 3b, 4a, 4b) have now been developed. The triene system has been constructed by an efficient stereoselec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This further emphasizes the impact of vitamin D and VDR for innate and adaptive immunity and suggests that these areas should be further explored for a commercial application …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This further emphasizes the impact of vitamin D and VDR for innate and adaptive immunity and suggests that these areas should be further explored for a commercial application …”
Section: Discussionmentioning
confidence: 89%
“…The Supporting Information is available free of charge on the ACS Publications website at DOI: 10.1021/acs.jmedchem.9b00208. Table S1 describing all 143 publically available VDR ligand crystal structures with individual hyperlinks to the PDB and PubMed databases and citations of refs (PDF) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that this theoretical hydrogen bonding pattern of analogue 5b is similar to that observed in the crystallographic structures of Gemini and the superagonist Gemini72 analogues, in complex with a wild-type zebrafish VDR(LBD). We have previously found that 1,25D analogues that bind significantly in silico are also biologically active . The promising docking results for 5a – c accordingly encouraged us to pursue their synthesis to further study the structure–activity relationships of vitamin D analogues.…”
Section: Resultsmentioning
confidence: 99%
“…We recently designed and synthesized new active analogues of 1α,25-(OH) 2 D 3 on the basis of simulation studies of their docking in the human VDR(LBD) . In silico, all these new analogues bind significantly to the Moras VDR(LBD) .…”
Section: Introductionmentioning
confidence: 99%